Disclosure obligations on selected European Alternative Investment Markets − comparison and conclusion - Fijałkowska, Dominika; Muszyński, Michał; Pauka, Marek (Wymogi informacyjne raportów spółek notowanych na Europejskich Alternatywnych Systemach Obrotu – analiza porównawcza, 2012)
The article’s objective is a comparison of selected European Alternative Investment Markets (AIMs) in the context of disclosure obligations and the evaluation of New Connect formalisation degree. AIMs, as distinct from the main stock exchanges, are regulated only by local stock exchanges which is the reason for significant differences in obligations for issuers, investors and third parties. Also disclosure obligations are characterised by different level of minuteness. The main peculiarities which distinguish each market are the different disclosures methods of publications and the particular regulations of the Italian and Polish markets, which is a consequence of their origin
Nauki o Finansach = Financial Sciences, 2012, Nr 1 (10), s. 141-154
Keywords: European Alternative Investment Markets; alternatywne systemy obrotu; disclosure obligations; investor protection; obowiązki informacyjne w raportach; ochrona inwestora